MINAT MAHASISWA ANGGOTA INTERNATIONAL ASSOCIATION OF STUDENT IN AGRICULTURAL AND RELATED SCIENCES (IAAS) INDONESIA UNTUK BEKERJA DI SEKTOR PERTANIAN - Hasna Putri; Rani Andriani Budi Kusumo (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2020)
Agriculture sector is a sector that take a lot of labor in Indonesia. There is a promblem with employment in agriculture sector, the high amount of old age labor and labor with low education. The lack of interest with agriculture from young generation is one of the causes that problem is happened. IAAS Indonesia is an organization that can be a place for young generation to give their aspiration about agriculture in Indonesia. The purpose of the study was to analyze (1) the interst to work in agriculture field of student as a part of IAAS Indonesia and (2) a correlations between interest factor and the interest to work in agricultural field. Data is collected by using questionnaires with a member of IAAS Indonesia. This research is a quantitative study  with descriptive survey techniques . The study was conducted to 88 students through the use of the Slovin formula.The result show that an interest to work in agriculture field for student of member IAAS Indonesia is in high category and factor which connect with student interest are  personality of the student, emotional factor, economics motive and condition of the work.